Benefits, Risks, and Best Practice in Regional Anesthesia: Do We Have the Evidence We Need?. Issue 6 (1st October 2010) - Fischer, Barrie
Abstract : For more than 25 years, Regional Anesthesia has challenged anesthesiologists to determine whether it offers real benefits in terms of patient outcome from major surgery, compared with general anesthesia. Although there is good evidence that regional analgesia offers superior pain relief to systemic opioid analgesia, evidence to support improved outcome from surgery remains elusive. Although many publications appear to support the hypothesis, others show no benefit, and the lack of properly conducted, large studies makes it difficult to draw any evidence-based conclusions in favor of regional anesthesia. Given that all major regional techniques have the potential to cause significant risks to patient outcome, it is incumbent on all anesthesiologists to balance the intended benefits against the significant adverse events associated with regional techniques. We are beginning to develop an evidence base for both the benefits and risks of regional anesthesia, when used for specific patient groups and for specific surgical procedures. This presentation looks at some of the evidence and examines how it can be used to develop guidelines for best practice.